Stroke and Anxiety: A Review of Pathophysiological Mechanisms, Clinical Relevance, and Treatment Strategies - Liao Ziqi; Huang Ju (BIO Web of Conferences)
Stroke, a major global health issue, results in significant morbidity and mortality. Post-stroke anxiety complicates recovery and impacts quality of life for patients and their families. This review examines the mechanisms, clinical features, diagnostic methods, and management of post-stroke anxiety. The interplay between stroke-related deficits and anxiety requires a multidisciplinary approach. Accurate diagnosis relies on clinical scales and neurocognitive tests. Management includes medication, cognitive-behavioral therapy, and lifestyle changes. It is crucial to understand the biological interactions between stroke and anxiety to develop target treatments. Progress in neuroimaging and animal models have provided guidance for relevant scientific research and clinical strategies. Meanwhile, a whole approach that integrates pharmacology, psy- chotherapy, and supportive interventions has optimized rehabilitation and health outcomes.